Letter - Winstanley, E.
029-0075-001 Telegraphic address: "Wholesale Manchester" Telephone: Blackfriars 1212 Extension No. Please address your reply: Co-operative Wholesale Society Limited, Exporters, Buying and Shipping Agents, 1, Balloon Street, Manchester, 4. Cable Codes: A.B.C., 6th and 7th editions; Western Union 5 letter; Bentley Complete Phrase; Bentley Second Phrase; A.1. MARCONI, and Private. Our reference EXPORT ST/HP. 345 Your reference 17th December, 1937. The Trades union Congress General Council, Transport House, Smith Square, LONDON. Dear Sirs, Further to correspondence exchanged between us relative to your enquiry in respect of Food Stuffs for shipment to Barcelona, we beg to advise that we have now completed our investigations into the possibility of securing supplies of Condensed Milk and Milkpowder for despatch to the Spanish Frontier by rail. We have pleasure in giving you below quotations for - Minimum of 600 cases Full Cream Sweetened Condensed Milk, 48 x 1⅝ pints equivalent, 8/9% Butter Fat at the price of 13/9d per case delivered Cerbere, (French/Spanish Frontier). Minimum of 10 tons Full Cream Milkpowder, Roller process 26% Butter Fat packed in paperlined cases of 1 cwt at 65/- per cwt delivered Cerbere ( French / Spanish Frontier ). If you find these quotations of interest we shall be glad to have your observations in due course and meanwhile, remain, Yours faithfully, E. Winstanley Export Department. 292/946/29/75